SFC++: a tool for developing distributed real-time control software - Pardo Martinez, X C; Ferreiro Garcia, R (Microprocessors and microsystems, 1999)
This paper describes a visual tool for developing real-time control software for distributed industrial systems. The aim of this project currently in progress, is to obtain a visual programming environment which integrates both the advantages of object-oriented modelling for the design and simulation of systems and the power of modern distributed control systems (i.e. computers with real-time operating systems interconnected by means of industrial real-time networks). To bridge the gap between the object-oriented system model and the implementation level, at which we have multiple parallel tasks running on a network, sequential function charts (SFCs) are used as a standard formalism [12,16] for the description of system dynamics and control software programming.